3g-6(g-8)=32

Simple and best practice solution for 3g-6(g-8)=32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3g-6(g-8)=32 equation:


Simplifying
3g + -6(g + -8) = 32

Reorder the terms:
3g + -6(-8 + g) = 32
3g + (-8 * -6 + g * -6) = 32
3g + (48 + -6g) = 32

Reorder the terms:
48 + 3g + -6g = 32

Combine like terms: 3g + -6g = -3g
48 + -3g = 32

Solving
48 + -3g = 32

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-48' to each side of the equation.
48 + -48 + -3g = 32 + -48

Combine like terms: 48 + -48 = 0
0 + -3g = 32 + -48
-3g = 32 + -48

Combine like terms: 32 + -48 = -16
-3g = -16

Divide each side by '-3'.
g = 5.333333333

Simplifying
g = 5.333333333

See similar equations:

| z^2=(z-4)(z+5) | | 1000=40x^2 | | 18-3.8t=7.39-1.9t | | 6x^2+72x+210=0 | | a^5-6a^4+a-6=0 | | -84=6g | | 8+6/-4=12 | | 1.5x+10.3=3.4x-3 | | 57=3+6(4x-7) | | 7(4+7b)=-70 | | 18-3.8t=7.36-19t | | 2x^2-102x+14=0 | | 5n+4-8n=(-5) | | (u+8)(u-4)= | | -24=4(2-8r) | | -(1+6x)=14-x | | ln(8-6x)-2ln(x)=ln(2) | | 25-18+4(-2)= | | 3-4q=10q+100 | | W+1-5=2w | | 3x^15*x-36=0 | | 5x^2-27x+10=0 | | 7=x/2+5 | | 5y-3(y-2)+3= | | Q=xy-xy^2 | | 5+2x=3(2x+4)-5(x-2) | | 10-4(2w+1)=6w-4(6+w) | | -38=2k | | m+3n=7n | | 5(n+2)=3/5(5+10n) | | 7+3(3-2x)=7x+3(3x-2) | | 12=a-(-18) |

Equations solver categories